New beginnings: the right to equality and early childhood care and education - Fredman, S; Donati, G; Naicker, S (Taylor & Francis, 2023)
While South Africa has seen important advances in the provision of early childhood care and education (ECCE), about 3.2 million children still lack access to any programme. Problems of access and quality are most pronounced in the poorest communities. Even before Covid-19 forced many providers to close, these programmes were overcrowded, with poor infrastructure, and an under-paid and under-qualified workforce. ECCE is crucial for a child’s development, meaning that these inequalities are amplified in school and later life. This has knock-on effects for caregivers, particularly women, and their ability to access quality work. This article argues that the right to equality can be mobilised both in relation to the Constitution of the Republic of South Africa, 1996 and international law to address these disparities. By using a framework of substantive equality, we conclude that poverty, gender and race are potential grounds for discrimination both directly and indirectly. We further propose that resource-based justifications for limiting this right are unacceptable when budgets permit unequal resource distribution and contravene a government’s positive duty to fulfil the right to equality.